2018
DOI: 10.1017/s0021859619000091
|View full text |Cite
|
Sign up to set email alerts
|

Performance and utilization of nutrients in dairy cows fed with sunflower meal

Abstract: Non-decorticated sunflower meal (SFM) is a potential protein source for dairy cows with high-fibre content but high ruminal degradability. The effect of replacement of soybean meal (SBM) and wheat middlings (WM) with SFM on the intake, digestibility, microbial protein synthesis, nitrogen utilization and milk production of dairy cows was evaluated. Twelve Holstein cows were blocked by days in milk and distributed in three 4 × 4 Latin squares. Diets were formulated to be isonitrogenous and contained 550 g maize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…The protein degradability of SFM in the rumen has been reported to be high with values of a, b, and kd ranging from 23% to 39%, from 54% to 71% of CP, and from 6% to 27%/h, respectively (Alexandrov, 1998;Muia et al, 2001;Oliveira et al, 2019;Woods et al, 2003) ruminal degradability of CP in the SFCs used in the present study showed remarkably high values, especially for solubility with more than 70% CP. This high value could be an artifact due to the very fine particles of the feedstuff as passing through the polyester bag, but the DM solubilities were not very high, which suggests that the artifact hypothesis is not likely to be true.…”
Section: Discussionmentioning
confidence: 97%
“…The protein degradability of SFM in the rumen has been reported to be high with values of a, b, and kd ranging from 23% to 39%, from 54% to 71% of CP, and from 6% to 27%/h, respectively (Alexandrov, 1998;Muia et al, 2001;Oliveira et al, 2019;Woods et al, 2003) ruminal degradability of CP in the SFCs used in the present study showed remarkably high values, especially for solubility with more than 70% CP. This high value could be an artifact due to the very fine particles of the feedstuff as passing through the polyester bag, but the DM solubilities were not very high, which suggests that the artifact hypothesis is not likely to be true.…”
Section: Discussionmentioning
confidence: 97%
“…Foi desenvolvido um conjunto de dados para avaliar os sistemas energéticos a partir da análise de 181 observações de 16 dietas experimentais, oriundas quatro ensaios de alimentação de vacas leiteiras (OLIVEIRA et al, 2007;SOUZA et al, 2017;MOURA et al, 2018;e OLIVEIRA et al, 2019). A estatística descritiva do conjunto de dados está apresentada na Tabela 1.…”
Section: Methodsunclassified
“…O consumo de NDT foi obtido por meio de ensaio de digestão in vivo, utilizando a fibra em detergente neutro indigestível como marcador interno de excreção fecal. Oliveira et al (2019) avaliaram em quatro dietas experimentais, o efeito da inclusão de farelo de girassol (0,7,14 e 21% base de matéria seca) em dietas contendo 55% de silagem de milho e 45% de concentrado (base da matéria seca). Foram utilizadas 12 vacas da raça Holandesa no terço médio de lactação (média por tratamento entre 27 a 30 kg de leite/dia) em delineamento quadrado latino, em quatro períodos 21 dias cada, sendo 14 dias de adaptação e sete dias para coleta de dados sobre a produção e composição do leite, peso corporal, variação de peso corporal e consumo de NDT.…”
Section: Sistemasunclassified
See 1 more Smart Citation
“…It is possible to increase the nutritional value and reduce the deficiency of the protein [11], mineral components and easily digestible carbohydrates (sugars) in feed supplements using by-products of food processing plants (oil cake and oil meal of vegetable raw materials, beet molasses, etc.) [12,13].…”
Section: Introductionmentioning
confidence: 99%